4-Chloro-2-methyl-N-phenylbenzenesulfonamide - Gowda, B. Thimme (International Union of Crystallography, 2009)
There are two molecules in the asymmetric unit of the title compound, C(13)H(12)ClNO(2)S, with similar conformations. The orientations of the ortho-methyl groups in the sulfonyl benzene rings are in the direction of the N—H bonds of the sulfonamide groups. In the crystal, the molecules are each linked into centrosymmetric dimers through N—H⋯O hydrogen bonds and packed into a layered structure diagonally in the bc plane.